Thermomechanical Modeling and Experimental Characterization of Sheet Molding Compound Composites - Lang, Juliane (Schriftenreihe Kontinuumsmechanik im Maschinenbau, 2023)
The aim of this work is to model and experimentally characterize the anisotropic material behavior of SMC composites on the macroscale with consideration of the microstructure. Temperature-dependent thermoelastic behavior and failure behavior are modeled and the corresponding material properties are determined experimentally. Additionally, experimental biaxial damage investigations are performed. A parameter identification merges modeling and experiments and validates the models.